Partially crystalline epoxy networks with superior mechanical and adhesion properties. Issue 9 (2nd May 2016) - Arnebold, Andre; Wellmann, Stefanie; Hartwig, Andreas
ABSTRACT: The mechanical and adhesion behavior of cationically polymerized, partially crystalline epoxy networks is presented. For this, a reactive and a nonreactive poly(ɛ-caprolactone) (PCL) were used as the crystalline component for the formation of copolymers and polymer alloys, respectively. The trade-off between toughness on the one hand and glass transition temperature and mechanical strength on the other can be reduced by the presence of nanostructures in combination with small crystalline domains (< 1 μm), as in the case of epoxy/PCL-based polymer alloys. This structure–property relationship reveals that a certain degree of crystallinity leads to enhanced toughness in cationically polymerized epoxy networks.